Metallic powder injection molding using low pressure - Goncalves, A. C. (Elsevier B.V., 2001)
The demand by high performance materials that have to support severe service conditions at a reasonable cost has been forcing the powder metallurgy to improve constantly. The most recent and more important innovation in the area is the process of powder injection.Powder injection molding (PIM) is a technology capable of producing a new range of components from powders. This advanced technology overcomes the existent limitations in the forming of products with complex geometry. The process presents countless variations which are used in the industry today. Invariably, it consists of mixing the powders and a thermo-plastic binder, injecting the mass in the mold in the wanted form, debinding, sintering and making optional secondary operations, as for example, machinery.The purpose of this work is to review the metal injection molding techniques and apply the low pressure injection molding process to family of parts using metallic powder with 10 mum particle size. This work also comments the design and construction of a low pressure injection machine and injection molds. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: powder injection; mold; injection machine